Pengaruh Kontribusi Pendidikan, Ketenagakerjaan Dan Penggunaan Teknologi Terhadap Pertumbuhan Ekonomi Regional Di Sumatera Barat - Cici Kurnia Sari Lubis; Tengku Indah Syahfitri; Rizki Samora Muliana; Putri Salsabila; Nasrullah Hidayat (JURNAL ILMIAH EKONOMI DAN MANAJEMEN, 2025)
This research aims to analyze the influence of the contribution of education, employment and the use of technology to regional economic growth in West Sumatra. The method used in this research is a quantitative approach. The type of data used in this research is panel data. The data used is data from 19 Regencies/Cities of West Sumatra Province for 2017-2023. This research used secondary data, namely data obtained based on publications from related agencies. Data was taken by researchers from the Central Statistics Agency (BPS) OF West Sumatra Province.The result of this research show that employment and technology users have a positive and significant effect on regional economic growth, while the contribution of education has a positive and insignificant effect on regional economic growh. This research concludes that employment and technology users are very important for regional economicc growth, especially in the current era of internet technology.